Immune Reconstitution Inflammatory Syndrome Complicating Cryptococcal Meningitis in a Pediatric Heart Transplant Patient. Issue 2 (February 2022) - Miller, Chelsea; Daugherty, Reza; McCulloch, Michael; Stephens, Ina; Williamson, Peter R.
Abstract : Immune reconstitution inflammatory syndrome can be a complication of cryptococcal meningitis after immune reconstitution from antiretroviral therapy in HIV or reduced immune suppression in transplant recipients. In this case report, the authors discuss the diagnosis and management of cryptococcal-associated immune reconstitution inflammatory syndrome in a 10-year-old pediatric heart transplant recipient.